Susan Sherratt and John Bennet (eds). Archaeology and the Homeric Epics. - Lemos, Irene S. (Journal of Greek Archaeology, 2019)
The title, Archaeology and the Homeric Epics, does not do justice to the variety of papers published in this edited volume, that cover much more than the relation between the Homeric epics and archaeology. In the introduction, the editors (Susan Sherratt and John Bennett) highlight the need to move ‘beyond the old dichotomies between historicity and irrelevance and to bring a multi-disciplinary approach’ to the study of the epics (introduction, p. viii). Indeed, the introductory chapter summarises the diversity of such approaches and argues that the relationship of the epics and archaeology is intermingled without any of them having ‘the monopoly of power to shed light on the other’ (introduction, p. xv). The introductory chapter offers a valuable review of current debates and approaches to the study of epic poetry, as well as a summary of the contributions in the volume.